PENILAIAN KAPASITAS TERMINAL PETI KEMAS PELABUHAN TELUK BAYUR - Ratna Effiliani Putri; Rika Ampuh Hadiguna (Institut Transportasi dan Logistik Trisakti, 2016)
The objective of this paper is to examine the utilization and performance of port management so that it shows the level of operational effectiveness and efficiency of various port facilities. The assessment was conducted using the static and the dynamic capacity method, as well as the theoritical and the actual capacity. Overall, the findings show that the average utilization of container terminal facility in Teluk Bayur Port is still very low.